DAMPAK DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BALAI PEMBERDAYAAN SOSIAL BINA REMAJA (BPSBR) - Widwi Handari Adji; Wilma Zuarko Adji (Jurnal Co Management, 2021)
This is a causal associative study employing observation and questionnaire approaches to explore the impact of discipline and work environment on employee performance at BPSBR Cimahi, with a total of 50 respondents.The variables of discipline and work environment at BPSBR Cimahi were found to be in the good category. Employees are respectful and understand the importance of following all rules and regulations. Employees consider the physical environment to be quite comfortable and pleasant to work in, as well as non-physical variables such as the relationship between employees and supervisors, relationships with coworkers, and those participating in BPSBR.Employee performance is positively influenced by 0.461 or 46.1 percent when discipline and work environment variables are combined, whereas the remaining 53.9 percent is influenced by variables outside of this study.